Solvothermal synthesis of Mn–Zn Ferrite(core)@SiO2(shell)/BiOBr0.5Cl0.5 nanocomposites used for adsorption and photocatalysis combination - Taweesak Kaewmanee (2020)
© 2019 Elsevier Ltd and Techna Group S.r.l. Mn–Zn ferrite magnetic nanoparticles (MNPs) were deposited by silica shell for magnetic separation purpose. Following the formation of MZF(core)@SiO2(shell), MZF@SiO2/BiOBr0.5Cl0.5 nanocomposites were synthesized by a solvothermal route. X-ray powder diffraction (XRD), transmission electron microscopy (TEM), scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR) and Raman spectroscopy were used to characterize different phases, crystallinity, morphology and vibrational mode. Magnetic properties were investigated by a vibrating sample magnetometer (VSM). Chemical composition and valence state of the nanocomposites were analyzed by X-ray photoelectron spectroscopy (XPS), including energy band gap was determined by diffuse reflectance UV–visible spectroscopy. The MZF@SiO2/BiOBr0.5Cl0.5 nanocatalyst has strong adsorption in the dark and high photocatalytic performance in degrading of rhodamine B (RhB) dye under visible light irradiation. At the end of the fourth re-cycle, removal of 30 μM RhB solution was ~80% and the recycled photocatalyst separated by external magnetic field was 90 wt% of the original. In this research, calculated valence and conduction band edges were used to explain photodegradation mechanism of the MZF@SiO2/BiOBr0.5Cl0.5 nanocomposites.